Attending to Warning Signs of Primary Immunodeficiency Diseases Across the Range of Clinical Practice (2014)
ABSTRACT: Purpose: Patients with primary immunodeficiency diseases (PIDD) may present with recurrent infections affecting different organs, organ-specific inflammation/autoimmunity, and also increased cancer risk, particularly hematopoietic malignancies. The diversity of PIDD and the wide age range over which these clinical occurrences become apparent often make the identification of patients difficult for physicians other than immunologists. The aim of this report is to develop a tool for educative programs targeted to specialists and applied by clinical immunologists. Methods: Considering the data from national surveys and clinical reports of experiences with specific PIDD patients, an evidence-based list of symptoms, signs, and corresponding laboratory tests were elaborated to help physicians other than immunologists look for PIDD. Results: Tables including main clinical manifestations, restricted immunological evaluation, and possible related diagnosis were organized for general practitioners and 5 specialties. Tables include information on specific warning signs of PIDD for pulmonologists, gastroenterologists, dermatologists, hematologists, and infectious disease specialists. Conclusions: This report provides clinical immunologists with an instrument they can use to introduce specialists in other areas of medicine to the warning signs of PIDD and increase early diagnosis. Educational programs should be developed attending the needs of each specialty.